Meth wars: police, media, power - Linnemann, Travis (Alternative criminology series, 2016)
Introduction: the methamphetamine imaginary -- Walter White's death wish -- This is your race on meth -- Governing through meth -- The war out there -- Imagining methland -- Drug war, terror war, street corner, battlefield -- Epilogue: endless (drug) war